Aspek Sosio-Politik Petani Penyadap Karet Perempuan di Desa Hanua, Kecamatan Banama Tingang, Kabupaten Pulang Pisau, Kalimantan Tengah - Nurleni, Evi (IAIN Antasari Banjarmasin, 2014)
The politics can be referred to as the relations of power. If so, then the gender relation is a relation of power, between the parties that dominate and are subordinated, that is the gender power relations in the struggle for access and control between women and men in the management of resources in the household. So it is important to know how the access and control of women and men who works as rubber tappers farmers is in the public and domestic domain in the Hanua village. This study of the socio-political conditions of rural women is in qualitative-descriptive perspective, and the data is collected with the sharing of life techniques in which 20 men and women used as informants and is analyzed using the gender framework analysis (GFA) or the Harvard analysis techniques. Hanua is the village in Kahayan watershed, where the main livelihood of the population is rubber tapper farmers. Actually, the Dayaks do not distinguish the status of men and women in the public sphere, but there is a distinction in the exercise of power in domestic and public environments, which the men power is higher than women. This is reflected from unequal womenâs access and control, both in the management of family income and investment.